Addressing Latency Issues in 2D to 3D Conversion: Deploying Available Synthetic Database - N. L. Manasa (International Journal of Informatics and Communication Technology (IJ-ICT), 2018)
Conventional 2D to 3D rendering techniques involve a sequential process of grouping of the input images based on edge information and predictive algorithms to assign depth values to pixels with same hue. The iterative calculations and volume of data under scrutiny to assign ‘real-time’ values raise latency issues and cost considerations. For commercial consumption, where speed and accuracy define the viability of a product, there is a need to reorient the approach used in the present methodologies. In predictive methodologies one of the core interests is achieving the initial approximation as close to the ‘real’ value as possible. In this work, ‘synthetic’ database is used to provide the first approximation through comparison techniques and fed to the predictive tool. It is believed that this work will provide a basis for developing an efficient 2D to 3D conversion methodology.